Drying kinetics, total bioactive compounds, antioxidant activity, phenolic profile, lycopene and β-carotene content and color quality of Rosehip dehydrated by different methods - Goztepe, Berna; Kayacan, Selma; Bozkurt, Fatih; Tomas, Merve; Sagdic, Osman; Karasu, Salih (ELSEVIER, 2022)
This study aimed to determine the effect of different drying methods namely, hot air drying (HAD), freeze-drying (FD), vacuum drying (VD), and ultrasound-assisted vacuum drying (USVD) on drying kinetic, total bioactive compounds, lycopene and beta-carotene, phenolic composition and color quality of rosehip. Drying times of the rosehips for USVD, VD, and HAD were 180, 300, and 1140 min, respectively, indicating that USVD significantly reduced drying time of rosehip. The results of total bioactive compounds, lycopene and beta-carotene, phenolic composition showed that FD resulted the highest bioactive compounds, followed by VD, USVD, and HAD. DPPH and CUPRAC results showed that FD dried samples showed highest antioxidant activity than fresh and all dried samples while HAD showed lowest antioxidant activity. USVD and FD exhibited a lower Delta E value than HAD and VD, indicating that they had similar color properties to the fresh sample. USVD resulted in lower drying time and color change than VD and HAD, while USVD showed lower bioactive compounds retention than VD. This study suggested that USVD could be used as an alternative to HAD due to its lower drying time and higher bioactive compound and color retention than HAD.
Keywords: Ultrasound assisted vacuum drying; Phenolic profile; CUPRAC; Carotenoids; VITAMIN-C; HOT AIR; VACUUM; ULTRASOUND; FRUITS; ATMOSPHERE; CAPACITY; EXTRACTS; STORAGE; L.; Food Science & Technology